2015
DOI: 10.21831/reid.v1i1.4900
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening vocational character for polytechnic education which has non-production-based curriculum

Abstract: The vocational character of polytechnic education has declined in the last ten years, especially for polytechnic which has non-production-based curriculum. This research aims to reveal factors which have contribution in the devocationalization of polytechnic education, and to find out the alternative solution to revocationalize by considering the current condition and the future demand. This study applied qualitative approach supported by quantitative data that involved three polytechnics in Bandung and Malang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Meanwhile, six functions of education management have been proposed (Sumarti et al, 2015;Li, 2017;Anwar et al, 2013); namely: planning, organizing, mobilizing, coordinating, directing, and supervising. Handayani & Brodjonegoro (2015) also confirmed that management is a process that runs effectively and efficiently if an organization implements its management functions properly and appropriately. Furthermore, the function of management is associated with the initial and crucial part that leads to the effectiveness of other management functions.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Meanwhile, six functions of education management have been proposed (Sumarti et al, 2015;Li, 2017;Anwar et al, 2013); namely: planning, organizing, mobilizing, coordinating, directing, and supervising. Handayani & Brodjonegoro (2015) also confirmed that management is a process that runs effectively and efficiently if an organization implements its management functions properly and appropriately. Furthermore, the function of management is associated with the initial and crucial part that leads to the effectiveness of other management functions.…”
Section: Resultsmentioning
confidence: 61%
“…Individual behaviours can be also personal and subjective due to diverse interests among members even though they are intended to reach organizational goals. Furthermore, Handayani & Brodjonegoro (2015) shed light on three factors contributing to individual behaviours in an organization: (1) biographical characteristics; (2) ability; and (3) learning. The first characteristic is linked to innate personality within an individual, i.e., age and gender.…”
Section: Resultsmentioning
confidence: 99%
“…The time allocated to English language in public schools was totally inadequate. The participants (n= 6) also said that European countries were successful in language teaching because their syllabus and curriculum were production-based and that Turkey should prepare new syllabi and curricula that emphasize oral skills [40].…”
Section: Resultsmentioning
confidence: 99%
“…The difference is due to the environmental conditions of the area occupied. The results of Jennings, Mitchell, & Hannah (2014), Handayani & Brodjonegoro (2015), and Freeks (2015) concluded that the environment greatly influences character formation.…”
Section: Badrun Kartowagiranmentioning
confidence: 99%